Patent Foramen Ovale Closure and Medical Therapy for Cryptogenic Stroke: Evidence from Randomized Controlled Trials and Beyond - Khan, Razi (Cardiology and Cardiovascular Medicine, 2020)
There has been substantial investigation recently into the role of patent foramen ovale (PFO) closure for treatment of patients with cryptogenic stroke (CS). In this review, the background, results and limitations of 6 randomized controlled trials (RCTs) comparing PFO closure with medical therapy (MT) for CS are summarized. Methodologic and treatment-related differences between older and newer trials are outlined and serve as potential sources for discrepancy in results obtained. In particular, the selection of patients with “high-risk” anatomic features of PFO and continued use of antiplatelet therapy were important reasons for the benefit of PFO closure demonstrated in newer RCTs. The review also examines the association of PFO with CS in older patients, as well as discussing the role for PFO closure in these patients who were largely excluded from large RCTs. Thus far, direct comparisons of PFO closure and MT in older patient cohorts are lacking, with results from small, nonrandomized studies demonstrating inconsistent conclusions about differences in recurrent embolic event rates between older and younger patients after device implantation. Finally, this review discusses limitations in the evidence for use of oral anticoagulation compared with antiplatelet therapy in patients with CS and PFO not undergoing PFO closure.